Business Legality Training in the Context of Strengthening the Higher Education Entrepreneurship Ecosystem - Anwar, Mashuril; Nugroho, Handoyo Widi; Zatika, Dinda Anna; Lilyana, Besti; Yuniwati, Yuniwati; Omega, Jessica Anatasya (PT FORMOSA CENDEKIA GLOBAL, 2023)
This service activity aims to provide education to IIB Darmajaya students who receive the P2MW program regarding business legality. Apart from that, this activity also aims to assist in registering the legal entity PT. Individuals and NIB for IIB Darmajaya student businesses receiving the P2MW program. This goal is achieved by conducting outreach, discussions, and the practice of registering PT legal entities. Individuals and NIB. The results of the activity show that business legality plays a strategic role in strengthening the university's entrepreneurial ecosystem. This activity implies that the efforts of IIB Darmajaya students who receive the P2MW program obtain a statement letter and certificate of registration for the establishment of a PT Legal Entity. Individual and NIB certificate.